2010
DOI: 10.1111/j.1472-765x.2010.02843.x
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance in Listeria species isolated from catfish fillets and processing environment

Abstract: Aims:  To investigate the susceptibility of 221 Listeria spp. (86 Listeria monocytogenes, 41 Listeria innocua and 94 Listeria seeligeri‐Listeria welshimeri‐Listeria ivanovii) isolated from catfish fillets and processing environment to 15 antibiotics. Methods and Results:  Listeria isolates were analysed by disc‐diffusion assay for their resistance to 15 drugs. All isolates were resistant to cefotaxime and clindamycin but were sensitive to ampicillin, cephalothin, chloramphenicol, erythromycin, gentamycin, kana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
48
3
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 26 publications
6
48
3
2
Order By: Relevance
“…However, increasing reports of Listeria strains isolated from various sources that are resistant to penicillin, ampicillin, tetracycline, streptomycin, clindamycin, and even oxacillin and vancomycin represent a major public health concern [9][10][11]. The genetic mechanisms responsible for these resistances are an important research topic, given that L. monocytogenes can acquire resistance genes from, and transfer them to, enterococci, staphylococci, and streptococci [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…However, increasing reports of Listeria strains isolated from various sources that are resistant to penicillin, ampicillin, tetracycline, streptomycin, clindamycin, and even oxacillin and vancomycin represent a major public health concern [9][10][11]. The genetic mechanisms responsible for these resistances are an important research topic, given that L. monocytogenes can acquire resistance genes from, and transfer them to, enterococci, staphylococci, and streptococci [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…in tilapia and its water was relatively higher than catfish and its water (Table 1). Other study found that Listeria was found in tilapia and catfish (Chen et al, 2010;Jaleewar et al, 2007). This study found 3 isolates of L. ivanovii isolated from catfish, 2 isolates of L. ivanovii, 2 isolates of L. grayi and 1 isolates of L. welshimeri isolated from tilapia.…”
Section: Resultsmentioning
confidence: 91%
“…However, catfish and tilapia are potential agents of pathogenic bacteria such as Listeria sp. (Chen et al, 2010;Jaleewar et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies also indicated that L. innocua is the most prevalent Listeria species found in food products (27,35,46). This may be related to differential selection during enrichment and recovery procedures, or because L. innocua is simply more common in the environment than L. monocytogenes (12,41). According to the studies L. innocua grows faster than the pathogenic species in enrichment broths therefore with the L. monocytogenes both species are present almost the same levels (35).…”
Section: Discussionmentioning
confidence: 95%